2019
DOI: 10.1111/1365-2745.13134
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of modern pollen and plant richness across northern Europe

Abstract: Sedimentary pollen offers excellent opportunities to reconstruct vegetation changes over past millennia. Number of different pollen taxa or pollen richness is used to characterise past plant richness. To improve the interpretation of sedimentary pollen richness, it is essential to understand the relationship between pollen and plant richness in contemporary landscapes. This study presents a regional‐scale comparison of pollen and plant richness from northern Europe and evaluates the importance of environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 72 publications
6
35
0
Order By: Relevance
“…Second, the over-or underrepresentation of taxa may strongly influence diversity estimates. For example, many species many be underrepresented by pollen at low elevation, causing an underestimation of diversity (Reitalu et al, 2019). This suggestion is supported by our diversity estimates based on the original pollen count data (Appendix S4, which show increases instead of decreases with elevation.…”
Section: Decreasing Diversity With Elevation Is Not Captured By Polsupporting
confidence: 59%
See 1 more Smart Citation
“…Second, the over-or underrepresentation of taxa may strongly influence diversity estimates. For example, many species many be underrepresented by pollen at low elevation, causing an underestimation of diversity (Reitalu et al, 2019). This suggestion is supported by our diversity estimates based on the original pollen count data (Appendix S4, which show increases instead of decreases with elevation.…”
Section: Decreasing Diversity With Elevation Is Not Captured By Polsupporting
confidence: 59%
“…Our results are in agreement with some studies (Gosling et al, 2018) but in disagreement with a review that compares diversity from pollen and vegetation (Birks et al, 2016). Studies that find an agreement between both measures of diversity are often measured in flat (Jantz et al, 2014) or temperate ecosystems (Felde et al, 2016), at coarser scales (Matthias et al, 2015;Reitalu et al, 2019), do not use actual diversity measured from the vegetation (Weng et al, 2007), or are based on very large pollen sums (Meltsov et al, 2011).…”
Section: Decreasing Diversity With Elevation Is Not Captured By Polsupporting
confidence: 53%
“…Pollen identification yields different taxonomic levels: rarely species, but often genera and sometimes only family level. The relationship between pollen and plant taxonomy is a form of higher-taxon surrogacy 20 and comparative studies have shown that spatial patterns in plant diversity are captured by pollen 2124 . To evaluate the effect of higher-taxon surrogacy in this study we explore these patterns at two hierarchical levels based on pollen morphology following harmonisation of the full dataset.…”
Section: Introductionmentioning
confidence: 99%
“…3b). There has been a similar increase in the number of species and diversity due to modest human activity, which we call generic human impact, in large scale areas of vegetation [63][64][65] and overall richness in the Eukaryote domain [29] in lakes of northeastern Europe. Although the modest human activity increased the patchiness of the boreal and semi-boreal forest, offering more niches for various terrestrial species, the similar increase in the lake's ecosystem is intriguing.…”
Section: (B) Perturbation Periods and Their Association With Change Pmentioning
confidence: 99%